Pencapaian penyelidikan 2019 / Ainorkhilah Mahmood - Mahmood, Ainorkhilah (Jabatan Sains Gunaan, 2020)
*Geran penyelidikan *Kajian Hukum Kebersihan Pakaian Bernajis menggunakan Mesin Basuh *Green Synthesis of Murdania Lori- formis-Mediated Silver Nanoparticles: Exploring its Cytotoxic Properties. *An investigation on properties of Mi- tragyna speciosa (Ketum) as organic photo-electron generator by Metal- free Organic sensitizer injection model. *Computational 2D/3D structural mod¬elling and impedimetric interrogation of conformational changes for se¬quence specific binding of micro RNA -21 towards p-19 protein *Properties and Growth Mechanism of Novel Integrated Pulsed Electro¬chemical Etching of Porous GaN for Potential Optoelectronics Application.